Translational insights into pain mechanisms and balance impairments in aging: a cross-sectional study - Alshahrani, Mastour Saeed; Reddy, Ravi Shankar (Frontiers in Aging Neuroscience, 2025)
ObjectivesThis study aimed to investigate the association between pressure pain threshold (PPT), pain intensity, pain catastrophizing, and postural stability and to assess the impact of pain chronicity and duration on functional reach and posturographic outcomes in community-dwelling older adults.MethodsA cross-sectional study was conducted involving 136 older adults (mean age = 74.23 ± 6.52 years). Pain mechanisms were assessed using an algometer (PPT), the Numeric Pain Rating Scale (NPRS), and the Pain Catastrophizing Scale (PCS). Balance was evaluated via force plate posturography (sway metrics) and the Functional Reach Test (FRT). Covariates included Mini-Cog and Geriatric Depression Scale scores. Data were analyzed using Pearson correlations, multiple linear regression, and ANCOVA.ResultsSway velocity was significantly predicted by PPT (B = 0.47, p < 0.001), NPRS (B = −0.36, p < 0.001), PCS (B = −0.29, p = 0.001), Mini-Cog (B = 0.33, p = 0.003), and GDS (B = −0.18, p = 0.011), explaining 48% of the variance (R2 = 0.48, F(5,130) = 24.15, p < 0.001). Chronic pain was associated with reduced FRT performance (F = 9.45, p = 0.003), and longer pain duration predicted greater sway area (B = 0.014 ± 0.004, p = 0.001).ConclusionBoth sensory and cognitive-affective dimensions of pain, along with pain chronicity, are independently associated with postural stability impairments in older adults. These findings support the integration of multidimensional pain assessments in clinical balance evaluations.